2009
DOI: 10.4314/ijbcs.v3i1.42739
|View full text |Cite
|
Sign up to set email alerts
|

Effects of administration of sertraline, clozapine, amitriptyline and imipramine on brain serotonin, liver enzymes and blood chemistry of rabbit

Abstract: The chronic administration of sertraline, clozapine, amitriptyline and imipramine on brain serotonin, liver enzymes and blood chemistry of rabbits were investigated. Sixty rabbits were equally divided into 5 groups and each group was intraperitoneally administered 2 ml of 0.5 mg of the respective drug/kg body weight/day) and saline as control for 28 days. After 28 days, the rabbits were sacrificed; blood taken, liver and brain were excised. The concentration of total protein, serotonin, cholesterol and triglyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Serotonin does not cross the blood-brain barrier; however, it is abundantly present also in the peripheral tissues (e.g., gut), is accumulated by blood platelets, and uses the same transporter to cross membranes in the periphery as it does in the CNS. It has been shown that, following the fluoxetine administration, serotonin levels increase in blood plasma and serum (35,36) while they decrease in the platelets (36). The opposite result reached by Alvarez et al (37) may be due to difficulties entirely separating platelets and plasma (38).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Serotonin does not cross the blood-brain barrier; however, it is abundantly present also in the peripheral tissues (e.g., gut), is accumulated by blood platelets, and uses the same transporter to cross membranes in the periphery as it does in the CNS. It has been shown that, following the fluoxetine administration, serotonin levels increase in blood plasma and serum (35,36) while they decrease in the platelets (36). The opposite result reached by Alvarez et al (37) may be due to difficulties entirely separating platelets and plasma (38).…”
Section: Discussionmentioning
confidence: 93%
“…SSRI drugs such as fluoxetine are commonly thought to function by inhibiting the serotonin transporter SERT, a membrane protein involved in the transport of neurotransmitter serotonin from the synaptic cleft, thereby changing the serotonin levels and persistence in the synaptic cleft (34). It has been shown that administration of the SSRI drug Sertraline for 28 d in rabbits increases the serotonin levels in brain (35). Serotonin does not cross the blood-brain barrier; however, it is abundantly present also in the peripheral tissues (e.g., gut), is accumulated by blood platelets, and uses the same transporter to cross membranes in the periphery as it does in the CNS.…”
Section: Discussionmentioning
confidence: 99%
“…One of the key factors on which brain function depends is the availability of neurotransmitter molecule for release into synapse, this alteration in the neurotransmitter scale may therefore underlie the functional deficit displayed by the protein malnourished groups. In addition, dopamine alteration perturbs neural encoding, this suggests a clinical association with other dysfunctions such as anxiety and psychosis (Ebuehi et al, 2001, 2009; Kelly et al, 2017). In malnutrition condition, free radicals mediate tissue damage, due to the inadequate protective and repair mechanisms in the protein-deficient models (Feoli et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…It is suggested that tricyclic drugs could reverse HVS in a physiological way through their improvement in brain serotonin and then subsequently be discontinued [31]. Ebuehi previously reported that malnutrition, marijuana smoking and ethanol consumption all decreased serotonin in experimental animals [32][33][34], while the tricyclic drugs (Impramine or amitriptyline) produces a more pronounced increase in brain serotonin levels compared with antidepressants such as sertraline [35]. These observations suggest that serotonin is important in the condition of HVS and offers a possible explanation for the observed benefits of amitriptyline.…”
Section: Discussionmentioning
confidence: 99%